Deteksi Duplikasi Metadata File pada Media Penyimpanan menggunakan Metode Latent Semantic Analysis - Erlin Erlin; Boby Hasbul Fikri; Susanti Susanti; Triyani Arita Fitri (Jurnal Inovtek Polbeng Seri Informatika, 2020)
Metadata files help user find relevant information, provides digital identification, archives and conserves stored files so that they are easily found and reused. The large number of data files on the storage media often makes the user unaware of the duplication and redundancy of the files that have an impact on the waste of storage media space, affecting the speed of a computer in the indexing process, finding or backing up data. This study employ the Latent Semantic Analysis method to detect file duplication and analyze the metadata of various file types in storage media. The findings showed that Latent Semantic Analysis method is able to detect duplicate file metadata in various types of storage media thereby further increasing the usability and speed of access of the data storage media.